A cross-sectional study of functional movement quality in school-aged children - Sajad Bagherian; Khodayar Ghasempoor (BMC, 2022)
Abstract Background During the growth period, before and after maturity, considerable biological changes occur. It seems that these changes are related to neuromuscular patterns and have significant differences in the functional movements performed of young boys and girls during the maturation process. The current study aimed to look at the movement quality scores of school-aged girls and boys. Methods This Cross-Sectional Study assessed the movement quality of 700 school-aged boys and girls aged 8 to 17, divided into 10 groups of 35 girls and 10 groups of 35 boys. Movement quality was evaluated by the Fusionetics scoring system, which includes 7 tasks: two-leg squat, two-leg squat with heel raise, one-leg squat, push-up, shoulder, trunk, and cervical movements that require a person to complete different movement patterns. The data was analyzed using the Wilcoxon signed-rank and McNemar tests (p <0.05). Results This is the first study to our knowledge to examine the movement quality scores in a large school age child with Fusionetics. The overall results showed that the most errors were recorded in all age groups during the double leg squat, double leg squat with heel lift, single leg squat, and push-up and school-age children showed less errors during the shoulder movements, trunk/lumbar spine movements and cervical spine movements. Furthermore, younger girls and boys made more errors than older girls and boys. In relation to gender, this study found that girls scored better on the total Fusionetics score than boys. Conclusions The Fusionetics scoring system explains how well school-aged children perform fundamental movements. Under the guidance of coaches and physical educators, students' movement compensation should be assessed and relevant training interventions implemented. Taking steps to address movement compensation could help to avoid injuries and improve school-age children performance.